"Sobre el principio de cooperación entre cooperativas en la actualidad" (On the principle of cooperation among cooperatives today) - Alejandro Martínez Charterina (Boletín de la Asociación Internacional de Derecho Cooperativo, 2012)
The present situation has been defined by two key facts. Firstly, we are going through an extraordinarily intense persistent economic crisis and we are celebrating the International Year of Cooperatives in 2012, which has been declared by the United Nations with the slogan «Cooperative enterprises build a better world». Cooperatives have the advantage of facing the crisis from a more flexible position, making them more resistant than other types of enterprises. The reason behind this is the business model of coops, whose actions are adjusted to the cooperative principles and values that make them unique. The sixth cooperative principle, which is cooperation among cooperatives, is inevitably linked to solidarity and plays a key role in their cooperative identity